Desafios para a permanência dos jovens do campo no ensino médio integrado do Instituto Federal do Pará/Campus Rural de Marabá - Nascimento Sobrinho, Shauma Tamara do (2024)
This thesis inscribed in the line of research Work, Education and Social Movements, of the Graduate Program in Education, Faculty of Education of the University of Goiás, the main objective of this study is to analyze the permanence and success of the students of the Integrated High School Course in Agricultural, at Federal Institute of Pará – Rural Campus of Marabá. Our focus was mainly on students from rural areas of the Southeast of Pará, especially those gave up their training. The time frame comprised the period from 2014 to 2019, the years of entry of the first six regular classes. Bibliographic, documentary and field research were carried out for data collection, through the application of a closed questionnaire and semi-structured interviews with students, teachers and administrative support technicians. The result of the research showed that the great challenges for the permanence of students in school refer to financial difficulties and failures and retentions, due to the excess and pace of the activities required by teachers. It was also found that the actions of students’ assistance have not been sufficient to meet the demands of students in situations of socioeconomic vulnerability, due to the excess of documents required, the amounts made available, the periods of publication of the notices and the amount of financial aid offered.